Energy Auditing and New Possible Solutions to save energy - Eshan Sharma (International Journal of Advanced Science and Technology, 2020)
Today, most of the energy that we use is produced by non-renewable sources of energy which is not abundant in nature. Hence, our prime motive should always be towards saving energy wherever possible. Even a small step towards energy consumption may lead to large savings in long run. In this report, we have done the energy auditing of mega mess 1 of NIT Nagpur which serves food to approximately 500 students daily.Most of the energy in Mega Mess 1 is used in 2 forms i.e. in form of electricity to run the lights, fans and also in the form of cooking gas (LPG) for preparing the food. The total consumption of electricity is calculated by considering all the electric equipment installed in the building and their average working time. Further the amount of LPG (in kg) used every day is calculated with the help of a small survey. After this, the total cost involved is calculated in both electricity and cooking gas. The study of the layout of lighting arrangement in the building is done and checked for any improvements that can be done in the layout. At the end, some alternate options were considered and advised which will lead to considerable savings in energy. In this report we have done the energy auditing of the mess, calculated the per capita consumption of the same and also suggested some measures to improve the same along with its payback period